Three-dimensional simulation of lateral migration of fiber in a laminar channel flow. (15th December 2022) - Cui, Jingyu; Wang, Zhaokun; Liu, Yang; Jin, Yuzhen; Zhu, Zuchao
Abstract: The lateral migration of a neutrally buoyant fiber in a three-dimensional (3D) channel flow bounded by four walls is numerically studied using a generalized immersed boundary-lattice Boltzmann method. The slender fiber is modeled as an elastic Kirchhoff rod to well reproduce its bending and twisting behaviors. Our simulations first examined the lateral migration of a flexible fiber released at six typical positions. The results show that the fiber accumulate at an isosurface of a specific shear rate value regardless of its initial lateral position. Thus, it would be more physical to characterize fiber accumulation behavior by the accumulation shear rate ( γα * ) rather than the accumulation position. The fiber basically migrates laterally along the shear rate gradient when there is a discrepancy between the local and the accumulation (target) shear rates. For a fiber of medium flexibility, varying its initial position does not change its γα *, while it could impact its orbits and tumbling plane. Compared to planar Poiseuille flows, more complex fiber orbits with out-of-plane deformations are observable in channel flows, and the fiber could adjust its tumbling plane to adapt to the surrounding shear rate gradient during its lateral migration. Our simulation results further confirm that the tumbling rate of the fiber increases with the increasing local shear rate. The impact of the effective flexibility of the fiber (Λeff ) on its lateral migration is also explored by considering a broad range of effective flexibility (Λeff ). The results show that the Λeff relates to the γα * non-monotonically, and five monotone intervals are captured. The results would enrich our understanding of fiber accumulation behavior in 3D wall-bounded flows and may also shed light on how we can sort fibers/filaments in microfluidic devices. Graphical abstract: Image, graphical abstract